Innovation in Sugihwaras Village, Sidoarjo District as A Smart Village Based on Government Policy - Monicha Puspitasari; Jusuf Irianto; Sulikah Asmorowati; Mira Aulia (Jurnal Public Policy, 2023)
This research aims to analyze and describe the innovation of Sugihwaras Village, Sidoarjo Regency as a smart village based on government policy. The research method uses descriptive with a qualitative approach. Data collection techniques were conducted through interviews, observation, and documentation. The results show that the smart village in Sugihwaras Village is in the form of government administration system applications and public services made by village officials, computer training for underprivileged village children, integrated landfill management, eco-enzyme training, and adequate access to education, health, and information technology. The implementation of smart economy in Sugihwaras Village is still not evenly felt. Innovation in Sugihwaras Village is supported by the leadership of the village head who is sensitive to the condition of children in Sugihwaras Village. Culture is also an important factor in innovating in Sugihwaras Village, namely care and excellent service. The ability to innovate is that the teachers who are village officials and the Village Community Empowerment Agency have qualified skills in the computer field. The work team is still within the scope of village officials and village institutions, but will work with Muhammadiyah Sidoarjo University in providing certification. The performance of the village government in the Griya Sinau Digital (GSD) program is that training participants have increased and some participants have found jobs.